An analytical and evaluative study of financial policy in Algeria during the Corona pandemic - شعابنة رزيقة (Finance and Business Economies Review, 2023)
This study aims to analyze the two parts of fiscal policy (expenditure, taxes), which is the main pillar through which the state can influence economic activity effectively, provided that it is flexible, and this is what distinguished the spending policy in Algeria during the epidemic crisis of Corona, by taking a number of Precautionary measures to contain and confront the pandemic. The study concluded that the financial policy in Algeria was valued in its response to the repercussions of the pandemic, which was embodied in a number of solutions that strengthened the ability of the Algerian economy to overcome the effects of the epidemic crisis Corona.